Papa, my father : a celebration of dads - Buscaglia, Leo F. (Thorofare, N.J. : SLACK ; New York, N.Y. : Distributed to the trade by Morrow, 1989)
This commemoration to an immigrant father extols the many roles he played: husband, educator, philanthropist, philosopher, patriot and nurturer.
Keywords: Buscaglia, Leo F. -- Family; Buscaglia, Rocco Bartolomeo; Authors, American -- 20th century -- Family relationships; Italian Americans -- California -- Social life and customs; Fathers and sons -- United States